Work organisation and innovation - Cox, Annette; Rickard, Catherine; Tamkin, Penny (Dublin, 2012)
"Innovations in work organisation have the potential to optimise production processes in companies and improve employees’ overall experience of work. This report explores the links between innovations in work organisation – under the broader label of high performance work practices (HPWPs) – and the potential benefits for both employees and organisations. It draws on empirical evidence from case studies carried out in 13 Member States of the European Union where workplace innovations have resulted in positive outcomes."